Rare Cases of Multidrug-resistant Tuberculous Spondylitis in Saiful Anwar General Hospital: A Case Series - Asmiragani, Syaifullah; Risantoso, Tjuk; Yudistira, Andhika; Satriawan, Ery; Lesmana, Albert; Pribadi, Alva; Siahaan, Lasa Dhakka (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Ten percent of all tuberculosis patients may develop skeletal involvement, and the spine is the most common anatomical location. Tuberculous spondylitis is further complicated by the fast-acid bacilli resistance to the usual chemotherapy regimen (multidrug-resistant/MDR) and its complications. In this case series, we would like to present three MDR tuberculous spondylitis cases effectively treated with tailored chemotherapy regimens and surgical interventions. CASE REPORT: A series of three patients with MDR tuberculous spondylitis is presented. All three patients presented with back pain, lump, and weakness of both lower extremities. These cases were resolved with a combination of surgical intervention and tailored chemotherapy regiment after MDR resistant detected. Two cases were resolved completely, and only one patient had residual paresthesia on his legs. CONCLUSION: A combination of MDR antituberculous chemotherapy and surgical intervention leads to an excellent outcome, in which the patient can perform regular daily tasks without pain, even in complicated MDR tuberculous spondylitis cases.